Carbon Microspheres Composite PbO2 Anode to Enhance Electrode Activity for Degradation of Isopropylantipyrine: Kinetics and Mechanism. Issue 12 (1st December 2022) - Tao, Qibin; Lan, Hao; Wei, Lanlan; Chen, Lu; Weng, Mili; Dai, Qizhou
Abstract : An innovative CMS-PbO2 electrode was fabricated by combining hydrothermally synthesized carbon microspheres (CMS) on a PbO2 electrode by electrodeposition. Using the CMS-PbO2 electrode, the main factors affecting Isopropylantipyrine (PRP) degradation were studied. Under optimum process conditions, the concentration of PRP was 50 mg l −1, the applied current density was 30 mA cm −2, the electrolyte (Na2 SO4 ) concentration was 0.1 mol l −1, and pH was 7. The PRP degradation rate reached 100%, and chemical oxygen demand (COD) removal rate reached 43.42% after 120 min of electrochemical oxidation. Using field-emission scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, cyclic voltammetry, linear sweep voltammetry, and electrochemical impedance spectroscopy, the electrochemical performance of the two electrodes was discussed. The composite of carbon microspheres successfully improved the electrochemical activity of the electrode and its conductivity. Furthermore, the ability of the two electrodes to generate hydroxyl radicals was compared and the possible degradation pathway of PRP was considered. In addition, electrode stability and safety were evaluated by accelerated lifetime experiments and detection of lead ions in solution after electrochemical oxidation. The CMS-electrode was more stable and safer than the PbO2 electrode. The CMS-PbO2 electrode provides a new strategy for the treatment of pharmaceutical wastewater.